2009
DOI: 10.1089/jmf.2008.0166
|View full text |Cite
|
Sign up to set email alerts
|

Orally Delivered Microencapsulated Live Probiotic Formulation Lowers Serum Lipids in Hypercholesterolemic Hamsters

Abstract: Elevated serum cholesterol is a major risk factor for coronary artery disease. Nutritional therapies such as probiotics have been suggested to manage elevated cholesterol. This study investigates the cholesterol and triglyceride lowering potential of a microencapsulated feruloyl esterase-producing Lactobacillus fermentum 11976 (LF11976) probiotic formulation. Male Bio F(1)B hamsters were assigned to two groups to receive either the microcapsule probiotic formulation (containing LF11976 cells at 12.51 log colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 49 publications
2
36
0
1
Order By: Relevance
“…Promising research focuses on the microbial secretion and production of beneficial biologically active enzymes and proteins, including: ornithine decarboxylase for the treatment of autoimmune diseases and accelerated cell apoptosis [22], bile salt hydrolase for hypercholesterolemia [23;24], and bile transport and tolerance proteins for the efficient delivery of probiotics [25]. In recent studies, the products of another microbial protein, cinnamoyl esterase, have shown significant levels of antioxidant activity [10,26] and other effects, including stimulation of insulin secretion [17,27], prevention of oxidative stress [17], lipid peroxidation [28],cholesterol-lowering capabilities [9] and inhibition of diabetic nephropathy progression [29]. A product of hydrolysis activity of FAE,FA, is a well-characterised antioxidant [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Promising research focuses on the microbial secretion and production of beneficial biologically active enzymes and proteins, including: ornithine decarboxylase for the treatment of autoimmune diseases and accelerated cell apoptosis [22], bile salt hydrolase for hypercholesterolemia [23;24], and bile transport and tolerance proteins for the efficient delivery of probiotics [25]. In recent studies, the products of another microbial protein, cinnamoyl esterase, have shown significant levels of antioxidant activity [10,26] and other effects, including stimulation of insulin secretion [17,27], prevention of oxidative stress [17], lipid peroxidation [28],cholesterol-lowering capabilities [9] and inhibition of diabetic nephropathy progression [29]. A product of hydrolysis activity of FAE,FA, is a well-characterised antioxidant [10].…”
Section: Discussionmentioning
confidence: 99%
“…This molecule is a potent antioxidant able to neutralize free radicals, such as Reactive Oxygen Species (ROS) [1] which have been implicated in DNA damage [2], cancer [3], accelerated cell aging [4], obesity [5] and type 2 diabetes mellitus (T2DM) [5,6]. A number of gastrointestinal tract (GIT) bacterial strains have been shown to produce feruloyl esterase (FAE) [7][8][9][10][11][12], an enzyme that hydrolyses and releases free FA from its bound state. Orally ingested FA-producing lactic acid bacteria should demonstrate an increased bioavailability of FA due to increased FAE activity in the intestine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the therapeutic efficacy of the formulation, animals in the treatment group (n=12) received the microcapsule formulation containing 10 11 cfu of L.f. 11976 twice daily, a dose determined from previous work by our group [9]. The control group (n = 12) received empty microcapsules as treatment vehicle-control.…”
Section: Animal Diet and Experimental Protocolmentioning
confidence: 99%
“…절, 혈중 콜레스테롤 저하, 과민성 대장증후군 같은 위장관 질환의 개선 효과, 암 예방, 면역체계 조절, 지질대사 개선 등의 연구 결과 가 보고되고 있다 (Bhathena et al, 2009;Lye et al, 2009;Rafter, 2004;Baken et al, 2006;Kim et al, 2014;Kang et al, 2013) …”
unclassified